Determinants of stillbirth among mothers who gave birth at Bishoftu General Hospital, Ethiopia: using a Bayesian logistic regression model - Regassa, Yeshi; Lemi, Hunde; Charkos, Tesfaye Getachew (Frontiers in Global Women's Health, 2024)
IntroductionStillbirth remains a major public health problem in developing countries due to low health coverage and services. Approximately two million stillbirths occur every year; in particular, stillbirths are highly prevalent in low- and middle-income countries such as Ethiopia. However, there is scarce information available in Ethiopia regarding the determinants of stillbirth.MethodsA facility-based, unmatched case-control study was conducted at Bishoftu General Hospital from April 1 to April 30, 2023. A systematic random sampling technique was used to select samples of the study subjects. The collected data were entered into Epi-info version 7.2. A Bayesian logistic regression model was used in this study, with a 95% Credible interval to determine the association between independent variables and stillbirth. All analyses were performed using STATA version 17 software.ResultsA total of 403 (81 cases and 322 controls) participants were included in the study. The average age of participants was 26 years (SD: ±5.03). According to the adjusted model, mothers who attained a middle school [adjusted odds ratio [AOR] = 0.23; 95% credible interval [CrI]: 0.11, 0.43], diploma and above (AOR = 0.25; 95% CrI: 0.12, 0.46), rural residence (AOR = 2.55; 95% CrI: 1.11, 4.99), married women (AOR = 0.46; 95% CrI: 0.20, 0.93), ANC visits more than 4 (AOR = 0.35; 95% CrI: 0.17, 0.63), history of prior stillbirth (AOR = 8.71; 95% CI: 3.22, 17.69), previous history of abortion (AOR = 3.29; 95% CI: 1.13, 7.666), duration of labor more than 24 h (AOR = 3.71; 95% CI: 1.28, 7.83); normal birth weight (AOR = 0.39; 95% CI: 0.15, 0.57) were significantly associated with stillbirth.ConclusionsThis study revealed that maternal education, rural residence, marital status, history of prior stillbirth, ANC visit, previous history of abortion, duration of labor, and birth weight were identified as determinants of stillbirth. Pregnant mothers should be identified early and given appropriate care, including comprehensive prenatal care and other maternal services.